2017
DOI: 10.1137/16m1067275
|View full text |Cite
|
Sign up to set email alerts
|

Worst-Case Mechanism Design via Bayesian Analysis

Abstract: Budget feasible mechanism design is the study of procurement combinatorial auctions in which the sellers have private costs to produce items, and the buyer (auctioneer) aims to maximize her valuation function on a subset of purchased items under the budget constraint on the total payment. One of the most important questions in the field is "which valuation domains admit truthful budget feasible mechanisms with 'small' approximations to the social optimum?" Singer [Proceedings of the 51st FOCS, IEEE Press, Pisc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 43 publications
1
25
0
Order By: Relevance
“…We hope that our results may lead to new mechanisms and improved analysis for more general valuation classes. Indeed, given the same factor 2-approximation result of [BCGL17] for the promise version of the problem for a subadditive buyer, we are even so bold as to conjecture that the true approximation guarantee for a subadditive buyer is still 2 (leaving all computational considerations aside).…”
Section: Conclusion and Open Questionmentioning
confidence: 82%
“…We hope that our results may lead to new mechanisms and improved analysis for more general valuation classes. Indeed, given the same factor 2-approximation result of [BCGL17] for the promise version of the problem for a subadditive buyer, we are even so bold as to conjecture that the true approximation guarantee for a subadditive buyer is still 2 (leaving all computational considerations aside).…”
Section: Conclusion and Open Questionmentioning
confidence: 82%
“…All of our mechanisms are randomized and, in fact, random sampling is an essential building block in our approach, as in previous related works [2,6,10,34]. Designing deterministic mechanisms seems very challenging and, beyond additive functions [17,40], no deterministic, polynomialtime, budget-feasible O(1)-approximation mechanisms are known, except for some special cases [1,2,18,29,41].…”
Section: Introductionmentioning
confidence: 95%
“…For subadditive functions, Dobzinski et al [18] suggested a O(log 2 n)-approximation mechanism, and gave the first constant factor mechanisms for a special case of non-monotone objectives, namely cut functions. The factor for subadditive functions was later improved to O(log n/log log n) by Bei et al [10], who also gave a randomized O(1)-approximation mechanism for XOS functions, albeit in exponential time in the value query model, and further initiated the Bayesian analysis in this setting. 1 Amanatidis et al [2] suggested O(1)-approximation mechanisms for a subclass of non-monotone submodular objectives, namely symmetric submodular objectives, however their approach does not seem to generalize beyond this subclass.…”
Section: Introductionmentioning
confidence: 99%
“…All of our mechanisms are randomized and, in fact, random sampling is an essential building block in our approach. Obtaining a good estimate of the optimal value via random sampling has been crucial in previous works on budget-feasible mechanism design for monotone objectives as well [2,5,10,35]. Designing deterministic budget-feasible mechanisms seems very challenging.…”
Section: Introductionmentioning
confidence: 99%
“…For settings with additional combinatorial constraints, Amanatidis et al [1] and Leonardi et al [35] gave O(1)-approximation mechanisms for additive valuation functions subject to independent system constraints. There is also a line of related work under the large market assumption (where no participant can significantly 2 Bei et al [10] propose an O (1)-approximation mechanism for non-decreasing XOS objectives that runs in polynomial time in the much stronger demand query model. However, they discuss how to extend their result to general XOS functions via the use ofˆ (S ) = max T ⊆S (T ).…”
Section: Introductionmentioning
confidence: 99%